2019
DOI: 10.1515/hsz-2019-0182
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally versatile – arginine in bacterial post-translational protein modifications

Abstract: Post-translational modifications (PTM) are the evolutionary solution to challenge and extend the boundaries of genetically predetermined proteomic diversity. As PTMs are highly dynamic, they also hold an enormous regulatory potential. It is therefore not surprising that out of the 20 proteinogenic amino acids, 15 can be post-translationally modified. Even the relatively inert guanidino group of arginine is subject to a multitude of mostly enzyme mediated chemical changes. The resulting alterations can have a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 332 publications
(449 reference statements)
0
8
0
Order By: Relevance
“…Although the relatively inert guanidine group of arginine was previously thought to impede nucleophilic attack onto donor substrates, it is now clear that many bacterial enzymes have overcome this barrier. The enzymology and functional roles of arginine glycosylation, methylation, phosphorylation, and ADP-ribosylation were recently reviewed 14 .…”
mentioning
confidence: 99%
“…Although the relatively inert guanidine group of arginine was previously thought to impede nucleophilic attack onto donor substrates, it is now clear that many bacterial enzymes have overcome this barrier. The enzymology and functional roles of arginine glycosylation, methylation, phosphorylation, and ADP-ribosylation were recently reviewed 14 .…”
mentioning
confidence: 99%
“…High expression levels of PDCL-3 increased the sensitivity to hypoxia stress and impacted on the interaction with vascular endogenous growth factor receptor 2 (VEGFR-2) leading to regulating angiogenesis in Zebrafish and mouse. In E. coli , acetylation of arginine site of ribosomal protein L12 not only affected the regulation of cell cycle, but also enhanced the stress resistance of bacteria by enhancing the intra-molecular interaction of ribosomal stalk 21 . Sclerotia formation is to adapt to the environment change.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that K. pneumoniae in biofilms showed higher resistance to polymyxin than the planktonic cells ( Naparstek et al, 2014 ). This difference between protein level and phenotype may be caused by post-translational modifications of proteins ( Lassak et al, 2019 ). Defects in K. pneumoniae porins OmpK35 and OmpK36 (their E. coli homologs are OmpF and OmpC, respectively) could lead to reduced sensitivity to carbapenem ( Sugawara et al, 2016 ; Hamzaoui et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%